Chelonia. - Choo, Ling Miin. (2013)
Chinese people are well-known for their amazing power of observation and philosophical conceptualization. They utilized their skills to watch animals and their behaviors and that resulted in finding out their characteristics. This knowledge was then used to connect the animal traits with the humans. Many animals like tortoises were objects of philosophical inner meaning and it has been passed on in generations. Though these animals have deep significant meaning to the Chinese, they were mistreated with many unethical practices due to the misunderstanding of cultural practices and beliefs. Tortoise for example, often used as a symbol to determine a person’s life; longevity, however, do